1985
DOI: 10.1159/000242175
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hormones and Undernutrition on Brain Development in Newborn Rats

Abstract: High L-thyroxine (T4) and cortisol doses given to rats during the first 8 days of life and on the first day only respectively, produce decrease of body and brain weight and perturbances to brain energy substrates, i.e. glucose and ketone bodies. The same alterations are found in the undernourished rats from the prenatal period. The pituitary GH and TSH is decreased in the T4- and cortisol-injected animals. The plasma ACTH is decreased in the treated cortisol animals at 8, 12 and 22 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
2
4
1
Order By: Relevance
“…Mello et al [20], using an undernutrition model similar to ours, found a decrease in glycemia and insulinemia on the day of birth in rats submitted to a low-protein diet. In contrast to PascualLeone et al [17] and Yeh et al [18], we found a marked increase in liver glycogen levels in 7-and 10-day-old undernourished rats.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Mello et al [20], using an undernutrition model similar to ours, found a decrease in glycemia and insulinemia on the day of birth in rats submitted to a low-protein diet. In contrast to PascualLeone et al [17] and Yeh et al [18], we found a marked increase in liver glycogen levels in 7-and 10-day-old undernourished rats.…”
Section: Discussioncontrasting
confidence: 99%
“…The decreased glycemia in malnourished rats from 10 days of life and the increased ketonemia at 10 and 15 days of age corre spond to data reported by Escrivd et al [ 10] and by Pascual-Leone et al [17], but differ from those reported by Yeh et al [18], who found a decrease in both parameters in 14- Each value is the mean ± SEM for the number of animals indicated in parentheses. Total ketone bodies are given by sum of (5-hydroxybutyrate and acetoace tate.…”
Section: Discussionsupporting
confidence: 80%
“…Neither body nor brain weight showed significant differences between saline-and thyroxine-treated rats, such as are reported in the literature (Chen and Fuller, 1975;Balazs et al, 1977;Bass et al, 1977;Pascual-Leone et al, 1985). Yet, from the inspection of the individual data, it was apparent that some of the rats that had received the highest doses of thyroxine were distinctly small and that the individual variability of brain weight was rather large in the animals treated with higher doses.…”
Section: Resultsmentioning
confidence: 64%
“…The hormone primarily stimulates RNA synthesis (Blecher and Bar,198 l), and possibly the production of nerve growth factor (Sadiq et al, 1985). Neurons respond to thyroxine with increased metabolism and accelerated growth and proliferation (Sokoloff, 1977), which results in shifts in local cell numbers (Balazs, 1977;Bass et al, 1977), altered neuronal size (Moskovkin and Marshak, 1978), different lengths ofaxonal projections (Lauder, 1977), and altered balances between afferent projections (this study), not to mention more subtle biochemical changes (Rastogi and Singhal, 1974;Balazs et al, 1977;Pate1 et al, 1980;Rastogi et al, 198 1;Davis and Martin, 1982;Legrand, 1983;McCarty et al, 1983;Pascual-Leone et al, 1985).…”
Section: Discussionmentioning
confidence: 77%
“…Glucocorticoids have previously been reported to retard tissue growth, including that in the brain (11,12), as well as to inhibit proliferation of cells of neural and nonneural origin (13)(14)(15)(16). Glucocorticoids also stimulate cell differentiation and induce differentiation-dependent enzymes (17,18).…”
mentioning
confidence: 99%